Business Dispute Resolution through Arbitration and Mediation within the National Legal Framework - Junaidi, Junaidi; Hardyansah, Rommy; Putra, Arif Rachman (Journal of Social Science Studies, 2024)
This article examines the resolution of business disputes through arbitration and mediation using normative legal methods. The study focuses on the construction of regulations in Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, as well as mediation regulations in court through PERMA No. 1 of 2016 and relevant electronic court service tools. The analysis assesses how norms shape forum selection, organize jurisdiction, and connect private mechanisms with court authority at the stages of registration, enforcement, and annulment of arbitration awards. The results of the study show that the design of arbitration emphasizes the finality of awards and limits legal remedies, but still requires judicial support for enforcement through execution. In court mediation, the obligation to undergo mediation before the main case examination provides space for agreement-based settlements that can be strengthened as peace deeds with executory force. This article then formulates normative measures for assessing the performance of arbitration and mediation based on four parameters: legal certainty, enforceability of outcomes, total costs, and confidentiality. Legal certainty is tested through the clarity of clauses, the validity of the process, and the finality of the outcome. Enforceability is measured by the accuracy of decision registration, the smooth issuance of writs of execution, and the strictness of grounds for cancellation under Article 70 of Law 30/1999. Total costs are analyzed through cost structure, cost allocation, and compliance with examination deadlines. Confidentiality is assessed based on document access arrangements, party discipline, and electronic process security. These measures are used to assess the suitability between norms and transaction needs, including the ability of the mechanism to handle high-value disputes, recurring disputes, and disputes requiring temporary protection. The article emphasizes the distinction between the position of legislation and the rules of arbitration institutions that apply due to the choice of the parties, so that procedural assessments remain rooted in Law 30/1999 and PERMA. The practical implication is that companies need to prepare decision mandates, contract filing systems, and confidentiality protocols from the pre-litigation stage. For the courts, the consistency of enforcement services determines the credibility of alternative dispute resolution nationally.